An Endonasal Incision Adds a Second Vector of Manipulation During Percutaneous Reduction of Fractures Involving the Frontonasal Region. Issue 2 (June 2021) - Govind, Akshay; Jelmini, Jonathan
Study Design: A case report. Objective: To describe a modification of percutaneous reduction of frontal sinus and/or naso-orbito-ethmoid (NOE) fractures, adding an endonasal intercartilaginous incision to provide a second vector of manipulation. Methods: Case report with particular attention paid to surgical technique, followed by a brief review of relevant literature. Results: Technique : A Carroll-Girard screw is used to engage the thickest part of the anterior wall of the frontal bone through a stab incision just superior to the frontonasal junction. An endonasal intercartilaginous incision is then made and a Cottle elevator is introduced to manipulate the fracture from the inferior aspect of the frontonasal junction. The percutaneous screw and the endonasal elevator provide perpendicular vectors for manipulation, thereby improving ability to reduce fractures when percutaneous traction alone is not successful. The technique is described here in a patient with anterior table frontal sinus fractures combined with posteriorly displaced Markowitz type 1 NOE fractures. Conclusion: While percutaneous reduction of frontal sinus fractures has been previously described, this report adds a subtle but important modification both in indication and technique for optimizing reduction while maintaining surgical simplicity and minimizing morbidity.